(untitled) (Lex localis - Journal of Local Self-Government, 2024)
This study investigates the awareness, perceptions, and preparedness of Romanian construction developers and public procurement specialists in relation to nearly Zero-Energy Buildings (nZEBs), focusing on factors that influence their adoption. Employing a mixed-methods approach, the research analyzes 193 validated questionnaire responses and insights from interviews with four industry experts. The findings reveal a significant disparity in familiarity with nZEB, with developers exhibiting greater awareness than procurers. Compliance with regulations emerges as the primary driver for nZEB adoption, while high upfront costs and a scarcity of qualified workforce are major barriers. Additionally, the complexity and fragmentation of Romanian legislation on nZEB standards creates ambiguities and further hinders effective implementation. Despite these challenges, developers express moderate optimism about Romanian construction companies’ adaptability to future nZEB demands, whereas procurers remain less confident. The study underscores the critical role of proactive policy interventions, clear public procurement criteria, and collaborative strategies in aligning government-funded projects with energy efficiency goals. By addressing systemic barriers and fostering innovation, this research provides policymakers and stakeholders with actionable insights to facilitate a smooth transition to sustainable building practices in Romania.